2011
DOI: 10.1002/mrm.22923
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative lithium magnetic resonance spectroscopy in the normal human brain on a 3 T clinical scanner

Abstract: Lithium (Li) is a core for many neuropsychiatric conditions. The safe serum range of Li treatment is narrow, and regular monitoring by blood test is required, although serum levels are thought to be a poor indicator of Li concentration in the brain itself. Brain Li concentration can be measured by magnetic resonance spectroscopy. However, little data exist in the healthy human brain, and there are no studies of the relaxation properties of brain 7 Li at 3 T. Here, 11 healthy male subjects were prescribed Li ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…By exploiting the experimental T 1 and T 2 relaxation times of 7 Li in a subset of patients with BD, [Li] maps were established. Those global monoexponential T 1,mono and T 2,mono values were well within the range of previous reports (20,22,48). It is of interest to note here that the use of an SSFP sequence with an ultra-short TE minimizes the T 2 * weighting and reduces sensibly the T 2 weighting of the 7 Li image than a balanced SSFP sequence (28).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…By exploiting the experimental T 1 and T 2 relaxation times of 7 Li in a subset of patients with BD, [Li] maps were established. Those global monoexponential T 1,mono and T 2,mono values were well within the range of previous reports (20,22,48). It is of interest to note here that the use of an SSFP sequence with an ultra-short TE minimizes the T 2 * weighting and reduces sensibly the T 2 weighting of the 7 Li image than a balanced SSFP sequence (28).…”
Section: Discussionsupporting
confidence: 89%
“…It is at this point that nuclear magnetic resonance (NMR) provides a unique solution to detect and quantify in a noninvasive manner the local concentration of Li ([Li]). Indeed, Lithium-7 ( 7 Li), the most abundant stable Li isotope, possesses a good NMR sensitivity (w29% of 1 H), and its detection using in vivo 7 Li NMR spectroscopy has been performed successfully in animal models as well as in humans (19)(20)(21). More recently, 7 Li NMR spectroscopic imaging (22)(23)(24)(25) and magnetic resonance imaging (MRI) (26)(27)(28) have been applied for the noninvasive determination of brain Li distribution in patients with BD.…”
mentioning
confidence: 99%
“…Two early MRS imaging (MRSI) studies were performed on a clinical scanner, both at the relatively low magnetic field strength of 1.5 T (6, 7). Most recently, a one‐dimensional (1‐D) 7 Li MRSI study using a surface coil approach at 3 T was reported (8). Although these studies demonstrated the feasibility of the technique and localized signals from lithium were observed, the results were limited.…”
mentioning
confidence: 99%
“…A quantitative 7 Li magnetic resonance spectroscopy study of the normal human brain measured the in vivo T1 of 7 Li as 2.1 ± 0.7 seconds. The mean brain 7 Li concentration was 0.71 ± 0.1 mM, with no significant difference between grey and white matter, and the mean serum concentration was 0.9 ± 0.16 mM [73]. A later quantitative study on bipolar patients stable on long-term lithium treatment demonstrated a biexponential lithium T2 relaxation in the majority of cases with an average short decay time of 5.3 ± 1.4 ms and an average long decay time of 68.2 ± 10.2 ms.…”
Section: Lithiummentioning
confidence: 83%